Tracing Arab-Islamic Inheritance in Madagascar: Study of the Y-chromosome and Mitochondrial DNA in the Antemoro - Capredon, Mélanie; Brucato, Nicolas; Tonasso, Laure; Choesmel-Cadamuro, Valérie; Ricaut, François-Xavier; Razafindrazaka, Harilanto; Rakotondrabe, Andriamihaja Bakomalala; Ratolojanahary, Mamisoa Adelta; Randriamarolaza, Louis-Paul; Champion, Bernard; Dugoujon, Jean-Michel (PLOS ONE, 2013)
Madagascar is located at the crossroads of the Asian and African worlds and is therefore of particular interest for studies on human population migration. Within the large human diversity of the Great Island, we focused our study on a particular ethnic group, the Antemoro. Their culture presents an important Arab-Islamic influence, but the question of an Arab biological inheritance remains unresolved. We analyzed paternal (n=129) and maternal (n=135) lineages of this ethnic group. Although the majority of Antemoro genetic ancestry comes from sub-Saharan African and Southeast Asian gene pools, we observed in their paternal lineages two specific haplogroups (J1 and T1) linked to Middle Eastern origins. This inheritance was restricted to some Antemoro sub-groups. Statistical analyses tended to confirm significant Middle Eastern genetic contribution. This study gives a new perspective to the large human genetic diversity in Madagascar.